Current practices in robotic surgery for distal ureter in children: results from an EAU robotic urology section (ERUS) survey - Mattioli, Girolamo; Genova Gaia, Luca; Carlucci, Marcello; Minervini, Andrea; Sendogan, Furkan; Silay, Mesrur Selcuk; John, Hubert; Fiorenza, Venusia (Frontiers in Pediatrics, 2026)
IntroductionThe robotic approach for uretero-vesical junction (UVJ) anomalies in children is still limited and debated. Both paediatric and adult urologists perform these procedures. This survey-based descriptive study aimed to evaluate different robotic approaches to the UVJ anomalies and their spread among ERUS Urologists performing robotic surgery in children, focusing on indications, technical aspects and outcomes.Materials and methodsA survey was distributed to ERUS members to gather data on paediatric patients treated for UVJ anomalies between January 2017 and December 2022. Data were collected on demographics, diagnoses, surgical details, complications, and postoperative outcomes.ResultsThree Centres participated in the survey. A total of 153 patients were included in the study. Centre 1 participated with a series of 6 patients: (4 D-RALUR, ND-RALUR). Centre 2 participated with a series of 67 patients (2 D-RALUR, 65 ND-RALUR). Centre 3 participated with a series of 80 patients (56 D-RALUR, 16 ND-RALUR and 7 UU). The surgery success rate varied from 50% to 100%. No life-threatening events were reported. The main complications were the need for further surgery due to persistent VUR or post-operative UVJ obstruction.ConclusionsRobotic approach to the distal ureter in children is still not widely performed by ERUS Urologists. The most performed procedure is ND-RALUR. Robotic-assisted distal ureter surgery seems to be safe and feasible in paediatric patients, but further studies and experience are needed. This survey provides a general overview of the robotic-assisted surgical approach to distal ureter disease in the paediatric population and its different popularity and outcomes.